Possible multiorbital ground state in CeCu2Si2 - Amorese, Andrea; Marino, Andrea; Sundermann, Martin; Chen, Kai; Hu, Zhiwei; Willers, Thomas; Choukani, Fadi; Ohresser, Philippe; Herrero-Martin, Javier; Agrestini, Stefano; Chen, Chien-Te; Lin, Hong-Ji; et al. (Physical review, 2020)
The crystal-field ground-state wave function of CeCu2Si2 has been investigated with linearly polarized M-edge x-ray absorption spectroscopy from 250 mK to 250 K, thus covering the superconducting (Tc=0.6 K), Kondo (TK≈20 K), and Curie-Weiss regimes. The comparison with full multiplet calculations shows that the temperature dependence of the experimental linear dichroism is well explained with a Γ(1)7 crystal-field ground state and the thermal population of excited states at around 30 meV. The crystal-field scheme does not change throughout the entire temperature range thus making the scenario of orbital switching unlikely. Spectroscopic evidence for the presence of the Ce 4f0 configuration in the ground state is consistent with the possibility for a multiorbital character of the ground state. We estimate from the Kondo temperature and crystal-field splitting energies that several percents of the higher lying Γ6 state and Γ(2)7 crystal-field states are mixed into the primarily Γ(1)7 ground state. This estimate is also supported by renormalized band-structure calculations that uses the experimentally determined crystal-field scheme.